The Analysis of Added Value of Cow Rumen into Compost Fertilizer in Kendari City Slaughterhouses (RPH) (Case Study of Ikhlas RPH Farmer Group Business) - Abdul Rahim Syah; La Ode Alwi; Munirwan Zani (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2023)
This study aims to analyze the added value of processing cow rumen into compost at the Kendari City Slaughterhouse (RPH). This research was conducted from August 2021 to April 2022 using a case study method on the Ikhlas Farmer Group business, with eight farmer group members who serve as informants. The variables of this study were the respondent's identity and the characteristics of processing cow rumen contents into compost. Analysis of the data used is quantitative data analysis with the Hayami method. The results showed that the added value from processing cow rumen into compost in Poasia District, Anggoeya Village, Kendari City was IDR. 5.511/kg, which has a high ratio with added value to product value (44%) and profit of IDR. 4,574/kg. with a profit rate of 83%.